Cardiovascular magnetic resonance insights into anomalies of the mitral valve apparatus in Fabry cardiomyopathy and hypertrophic cardiomyopathy - Tondi, Lara; Disabato, Giandomenico; D’Andria, Paolo; Attanasio, Andrea; Guida, Gianluigi; Pieruzzi, Federico; De Angeli, Giada; Canepa, Marco; Carrafiello, Gianpaolo; Piepoli, Massimo; Spagnolo, Pietro; Lombardi, Massimo; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background and aims: Despite different etiopathogenesis, Fabry Disease cardiomyopathy (FDc) and sarcomeric hypertrophic cardiomyopathy (HCM) share a similar hypertrophic phenotype, including anomalies of the mitral valve apparatus (AMVA). Some AMVA have been described in the pre-hypertrophic stage of both diseases. This cardiovascular magnetic resonance (CMR) study aimed to: i) compare AMVA between FDc and HCM with similar left ventricular hypertrophy (LVH) degree ii) assess whether AMVA represent an early and progressive alteration in FDc; iii) propose simple and reproducible measurements of AMVA. The study enrolled: i) 80 Fabry patients (20 patients LVH-/normal T1, 20 patients LVH-/low T1 and 40 patients LVH+), and ii) 40 patients with HCM. All patients underwent CMR. The LVH+ FDc and the HCM groups were matched for age, sex, body surface area and left ventricular (LV) mass. The following AMVA were measured on cine images: papillary muscles (PMs) hypertrophy (maximal diameter (Dmax) of anterolateral (Al) and posteromedial (Pm) PM), apical displacement, anteriorization of Al PM and anterior mitral valve leaflet (AMVL) elongation. Reference values for AMVA derived from matched healthy controls (n=40).Results: Both HCM and FDc LVH+ patients showed PMs hypertrophy, with a greater degree in the FDc LVH+ group (Dmax Al 16±3.4 vs. 15±3.1mm, p0.017; Dmax Pm 14±4.0 vs. 12mm (10.0-14.0), p0.039). Both HCM and FDc LVH+ patients showed PMs apical displacement (HCM 83% vs. controls 8%, p<0.001; FDc LVH+ (65%, p<0.001), with e greater prevalence in HCM. Anteriorization of Al PM was only evident in HCM (15±6.2 vs. controls 21±5.3mm, p<0.001). Elongation of AMVL was detected both in HCM and FDc LVH+ (HCM 29±4.0 vs. controls 24±2.9mm, p<0.001; FDc LVH+ 27±4.0 vs. controls 24±2.9mm, p<0.001). The prevalence of myocardial crypts was higher in HCM (HCM 75% vs. FDc LVH+ 48%, p0.012). Conclusions: we report greater PMs hypertrophy in FDc and a higher prevalence of PMs positional alterations and myocardial crypts in HCM. All AMVA enhanced with the progression of the FDc phenotype. We recommend including AMVA analysis using reproducible linear measurements on cine images during CMR assessment, to helpdifferentiating HCM from FDc and to facilitate early detection of cardiac involvement in FDc.